Implementation of Living Values Education Pancasila Values In the Generation of Indonesians - Fadlan Choirul Adillah (CV. Rayyan Dwi Bharata, 2022)
Pancasila today has experienced a process of marginalization and challenges in the life of society, nation, and state. This is reflected in the rise of negative behaviors to pursue personal or class interests in a way that is contrary to the five precepts in Pancasila. In turn, this can threaten the values of Pancasila in the younger generation today and in the future. This journal aims to find out the implementation of living values education of Pancasila values in the generation of the Indonesian nation. The research method used is descriptive qualitative with literature review sources. The results of the discussion are known that Pancasila education through living values education is carried out by integrating theoretical learning with practical learning. There are various interactive programs such as picture and picture learning, example non example, debate, to role playing. This is then expected to increase the sense of the younger generation how the value of Pancasila should be applied in everyday life, not only in the form of memorization of precepts, especially in the midst of today's globalization currents.